Accelerating field excitation, occurrence and evolution of electron beam near Jupiter - Maslov, V.I.; Fomina, A.P.; Kholodov, R.I.; Levchuk, I.P.; Nikonova, S.A.; Novak, O.P.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2018)
When electron beam, formed Io-Jupiter penetrates into Jupiter plasma the beam-plasma instability develops.
Then electron distribution function becomes wider by excited fields. These electrons cause UV polar light. The conditions of formation, properties, stability and evolution of a formed intensive double layer have been described.
Beam reflection leads to semi-vortex formation. Когда электронный пучок, образованный Ио-Юпитера, проникает в плазму Юпитера, развивается пучково-плазменная неустойчивость. Тогда функция распределения электронов становится шире, благодаря возбужденным полям. Эти электроны вызывают ультрафиолетовое свечение. Описаны условия формирования,
свойства, устойчивость и эволюция сформировавшегося интенсивного двойного слоя. Отражение пучка
приводит к образованию полувихря. Коли електронний пучок, утворений Іо-Юпітера, проникає в плазму Юпітера, розвивається пучковоплазмова нестійкість. Тоді функція розподілу електронів стає ширше завдяки збудженим полям. Ці електрони викликають ультрафіолетове світіння. Описано умови формування, властивості, стійкість і еволюція інтенсивного подвійного шару, що формується. Відбиття пучка призводить до утворення напіввихору.